Evaluation of antioxidant activity of 1,2,4-triazole derivatives in the initiation of free radical processes - I. M. Bilai; V. I. Dariy; A. V. Khilkovets; A. I. Bilai; I. F. Duiun (Zaporozhye State Medical University, 2024)
The activation of lipid free radical oxidation is a key stage in the development of many diseases and can lead to the emergence of related complications. To identify new synthetic compounds with antioxidant properties, it is necessary to conduct studies on various models of experimental free radical oxidation of biomolecules. Literature sources indicate that among the derivatives of 1,2,4-triazole, there is a significant number that possess high antioxidant activity. The aim of the study to assess the antioxidant properties of newly synthesized S-derivatives of 1,2,4-triazole through the inhibition of reactive oxygen species accumulation in the superoxide dismutase system. Materials and methods. To achieve this goal, we used one of the methods for assessing antioxidant activity by initiating free radical processes in vitro, specifically by inhibiting the accumulation of reactive oxygen species. Results. Twenty-three S-derivatives of 5-(thiophene-3-ylmethyl)-4-R-1,2,4-triazole-3-thiols were investigated. The most effective compound was sodium 2-((4-phenyl-5-thiophene-3-ylmethyl)-1,2,4-triazole-3-yl)thio)acetate, which exceeded the activity of both reference drugs. Following in activity was compound 22, 1-phenyl-2-((4-phenyl-5-(thiophene-3-ylmethyl)-4H-1,2,4-triazole-3-yl)thio)ethanol, which demonstrated an effect similar to that of emoxipine, while compound 7, 1-(3-fluorophenyl)-2-((5-thiophene-3-ylmethyl)-4H-1,2,4-triazole-3-yl)thio)ethanone, was slightly less active. Conclusions. It was established that among the new S-derivatives of 1,2,4-triazole, some exhibit significant antioxidant effects that are comparable to or exceed the efficacy of reference drugs.